Definition of interaction curves for the in-plane and out-of-plane capacity in brick masonry walls - Najafgholipour, M. A. (2014)
During an earthquake a wall is subjected to a three dimensional acceleration field and undergoes simultaneous in-plane and out-of-plane loading. The action of one type of loading on the wall affects the strength of the wall against another type of loading. In this paper, a numerical investigation, supported by experiments, is conducted aimed at deriving appropriate relations for the in-plane/out-of-plane capacity interaction in unreinforced brick walls. Through a comprehensive parametric study, the main affecting parameters are recognized and their influences on the capacity interaction are established. The parametric study indicates that the aspect ratio of the wall and the elastic and inelastic material properties in tension have the most influence on the level of the in-plane and out-of-plane capacity interaction in masonry walls. Based on the results of these investigations, representing empirical analytical relations for evaluating the interaction are derived and their accuracy is verified.